The Role of Transformational Leadership, Work Environment, and Work Motivation in Improving Employee Performance on People's Credit Bank (Survey on Bank BPR Nusantara Bona Pasogit 14 and Nusantara Bona Pasogit 19) - Mayson Manurung; Deden A. Wahab (PT. Anagata Sembagi Education, 2025)
Employee performance is an important factor that determines the success of an organization, especially in financial institutions such as Bank Perkreditan Rakyat (BPR). In the face of increasingly fierce banking competition, employee performance is a determinant of competitiveness and operational sustainability. However, there are still problems such as the application of transformational leadership in providing inspiration and intellectual stimulation, work environment conditions that do not support productivity, and reward systems that are not able to motivate employees optimally. These problems have an impact on the suboptimal performance of employees at BPR Nusantara Bona Pasogit. This study aims to determine the influence of transformational leadership, work environment, and work motivation on employee performance, both partially and simultaneously. The approach used is quantitative with descriptive and verifiable methods. Data was obtained through the distribution of questionnaires to employees and analyzed using path analysis with the help of statistical software. The results of the study show that transformational leadership, work environment, and work motivation in general are in the category of good enough to very good. Partially, all three variables have a positive and significant effect on employee performance, while simultaneously all three have a strong influence on performance improvement. Among the three, work motivation is the most dominant factor in influencing employee performance. These findings confirm that improving employee performance can be achieved through inspirational leadership, a conducive work environment, and an effective motivation system. The results of the research are expected to be input for the management of BPR Nusantara Bona Pasogit in increasing leadership effectiveness, creating a supportive work atmosphere, and strengthening work motivation to encourage employee performance in a sustainable manner.